Profit Growth: Influenced by Financial Performance and Moderated Firm Size - Budiharjo, Roy; Hapsari, Dini Wahjoe; Harianto, Rudi (Jurnal Ilmiah Global Education, 2024)
The purpose of this study is to analyze the effect of firm size moderation on financial performance on profit growth. Secondary data was collected as a sample of companies listed in the Infrastructure Sector listed on the Indonesia Stock Exchange for the period 2019-2021. The sampling in this study uses the purposive sampling method with the following criteria: (1) Infrastructure sector companies listed on the IDX in 2019-2021. The data needed in this study was taken from the Indonesian Capital Market Directorate (ICMD) 2019-2021. This study used multiple linear regression analysis where the partial test used the t statistical test and simultaneous testing using the ANOVA statistical test and before this test was carried out the classical assumption test was carried out. The results of this study show that sales, total asset turn over and return on assets do not affect profit growth, company size affects profit growth, company size is unable to moderate the relationship between sales, total asset turn over and return on assets on profit growth.